The trade‐off between the light‐harvesting and photoprotective functions of fucoxanthin‐chlorophyll proteins dominates light acclimation in Emiliania huxleyi (clone CCMP 1516). Issue 1 (24th June 2013) - McKew, Boyd A.; Davey, Phillip; Finch, Stewart J.; Hopkins, Jason; Lefebvre, Stephane C.; Metodiev, Metodi V.; Oxborough, Kevin; Raines, Christine A.; Lawson, Tracy; Geider, Richard J.
Summary Mechanistic understanding of the costs and benefits of photoacclimation requires knowledge of how photophysiology is affected by changes in the molecular structure of the chloroplast. We tested the hypothesis that changes in the light dependencies of photosynthesis, nonphotochemical quenching and PSII photoinactivation arises from changes in the abundances of chloroplast proteins in Emiliania huxleyi strain CCMP 1516 grown at 30 (Low Light; LL) and 1000 (High Light; HL) μmol photons m−2 s−1 photon flux densities. Carbon‐specific light‐saturated gross photosynthesis rates were not significantly different between cells acclimated to LL and HL. Acclimation to LL benefited cells by increasing biomass‐specific light absorption and gross photosynthesis rates under low light, whereas acclimation to HL benefited cells by reducing the rate of photoinactivation of PSII under high light. Differences in the relative abundances of proteins assigned to light‐harvesting (Lhcf), photoprotection (LI818‐like), and the photosystem II (PSII) core complex accompanied differences in photophysiology: specifically, Lhcf:PSII was greater under LL, whereas LI818:PSII was greater in HL. Thus, photoacclimation in E. huxleyi involved a trade‐off amongst the characteristics of light absorption and photoprotection, which could be attributed to changes in the abundance and composition of proteins in the light‐harvesting antenna of PSII.